Role of nursing and midwifery in mainstreaming genomics in Australia: mixed-methods study exploring scope of practice and strategies for implementation - Alexander, Kim E.; Farley, Morgan J.; Scanlon, Brighid; Duff, Jed (Frontiers in Genetics, 2026)
BackgroundThe integration of genomics into Australian health services offers significant benefits for the diagnosis and delivery of targeted treatments, but its success relies on a workforce equipped to deliver genomic-informed care. Nurses and midwives, Australia’s largest healthcare workforce, have the potential to play a key role in the integration of genomic care into mainstream services by enabling access to the diverse and geographically spread Australian population. To achieve this, it is imperative to clearly define their roles in genomic practice and identify specific educational and resource needs.MethodsA two-part, mixed-method study was conducted encompassing a state-wide survey and a range of semi-structured interviews. The state-wide survey (n = 81), aimed to establish agreement on the key domains of genomic-related care practice for nurses and midwives. The semi-structured interviews with key practice change stakeholders (n = 32) sought to identify the barriers and facilitators to implementing the genomic practice domains. Descriptive statistics were generated to summarise the quantitative findings. The qualitative data were analysed using content analysis, with the findings organised according to the Consolidated Framework for Implementation Research.ResultsThere was general agreement (>85%) that nurses and midwives should be involved, to varying extents, in 18 of the 31 domains of genomic-related care. The domains with the highest overall agreement included being able to identify clinical indicators of genetic susceptibility, ability to take a family history and have a general understanding of genomic information. The integration of genomics into nursing and midwifery faces several barriers, including unclear roles and responsibilities, system and organisational challenges, and a lack of tailored education. Key facilitators identified were dedicated nursing or midwifery roles, tailored, co-designed education, and collaboration with key stakeholders.ConclusionOur findings highlight the need for clearly defined roles and scope of practice for nurses and midwives, supported by tailored, co-designed workforce development programs and implementation processes. Such approaches are essential to meet the varied needs and competencies of nurses and midwives and to fully enable the benefits of accessible genomic care.